Determinants Of Patient Satisfaction At Bangun Purba Regional General Hospital, Deli Serdang Regency Through Hospital Image - Riana Tarigan; Yusniar Lubis; Audia Junita (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study analyzes the determinants of patient satisfaction at Bangun Purba Regional General Hospital, Deli Serdang Regency through the image of the hospital destination. The determinants themselves consist of reliability, responsiveness, assurance, empathy and physical evidence. This study uses a quantitative approach through an explanatory survey to analyze one or more variables that influence other variables and the causal relationship between variables is explained by the hypothesis. This study uses primary data with a questionnaire as a research medium with 90 respondents as patient respondents at Bangun Purba Regional General Hospital, Deli Serdang Regency. The sampling technique uses purposive random sampling. The validity test shows that each variable is greater than 0.192, indicating validity. The reliability test shows reliable results with values greater than 0.60. The hypothesis test shows that each variable is greater than 0.1986. The results of the study indicate that the determinants of Service Quality variable, namely the variables of Reliability, Responsiveness, Assurance, Empathy, and Physical Evidence, have a positive and significant impact on Patient Satisfaction through the Image of the Hospital.